2017
DOI: 10.9775/kvfd.2017.18405
|View full text |Cite
|
Sign up to set email alerts
|

Çin’de Kanatlı Hayvanlardan İzole Edilen Pasteurella multocida Suşlarının Moleküler Karakterizasyonu ve tonB Geni Açısından Genetik Analizi

Abstract: Pasteurella multocida (P. multocida) causes fowl cholera in birds and the pathogenesis and virulence factors involved are still poorly understood. TonB protein is a periplasmic protein prevalent in a large number of Gram-negative bacteria, as in Pasteurella, which is believed to be responsible for the import of ferric iron complexes across the outer membrane and plays a role as an important virulence factor to help bacteria to obtain nutrients. In this study, a total of 23 isolates of P. multocida were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(34 reference statements)
2
0
0
Order By: Relevance
“…These findings were similar to Many authors; Ewers et al, (2006), Shayegh et al, (2010 and Khamesipour et al, (2014) who recorded tox A genes in P. multocida isolates. Then all 16 P. multocida isolates that were applied for tox A gene detection were submitted for capsular typing by multiplex PCR and found that all isolates were positive to capsular type A with amplified fragment 1044 pb, these results were in agreement with Zhangcheng et al, (2018) who recorded that the capsular types of P. multocida were confirmed by multiplex PCR. As the results of multiplex PCR specific for capsular antigens of P. multocida, 22 strains (95.7%) were found type A with a 1044 bp amplified fragment, whereas 1 strain (4.3%) was type F with 851 bp length fragment.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…These findings were similar to Many authors; Ewers et al, (2006), Shayegh et al, (2010 and Khamesipour et al, (2014) who recorded tox A genes in P. multocida isolates. Then all 16 P. multocida isolates that were applied for tox A gene detection were submitted for capsular typing by multiplex PCR and found that all isolates were positive to capsular type A with amplified fragment 1044 pb, these results were in agreement with Zhangcheng et al, (2018) who recorded that the capsular types of P. multocida were confirmed by multiplex PCR. As the results of multiplex PCR specific for capsular antigens of P. multocida, 22 strains (95.7%) were found type A with a 1044 bp amplified fragment, whereas 1 strain (4.3%) was type F with 851 bp length fragment.…”
Section: Discussionsupporting
confidence: 74%
“…As for postmortem lesions, they include: haemorrhages in the heart, liver, gizzard and intestines besides white spots and necrotic foci in the liver and spleen as described by Abd-El-Rahman et al, (2009). In the present study, out of 220 ducks which suffer from duck septicemia examined, sixteen samples were positive to P. multocida (7.3 %) as obtained with Eid et al, (2019) who isolated P. multocida from ducks with proportion of (7.3%), but it is lower than the level reported by Zhangcheng et al, (2018) who isolated (13.4%) of P. multocida from ducks in china, (Bhattacharya, 2005) who recorded 18 isolates of P. multocida with a high percentage (77.77%) of P. multocida isolates that were recovered from ducks, Walaa and Lamyaa (2016) who isolated (63%) of P. multocida in duck flocks and who isolated (34%) P. multocida from sick ducks. These results are higher than the level reported by (Mbuthia et al, 2008) who recorded an isolation rate of 6.2% and (Muhairwa et al, 2001) who recorded that The prevalence of P. multocida was 7%.…”
Section: Discussionsupporting
confidence: 55%